Effectiveness of using liquid nitrogen cryogen in grinding to enhance the grinding performance of hard steel - Sharma A.; Chaudhari A.; Yusufzai M.Z.K.; Vashista M. (My University, 2025)
Grinding generates a lot of heat in the grinding zone area during operation. Therefore, it is important to keep the temperature under control by using various cutting fluids to get a good ground surface quality. The existence of a stiff air layer surrounding the abrasive wheel is known to waste most of the cutting fluid supply in the interface area between the abrasive wheel and workpiece. Due to the high grinding speed, stiff air layers prevent cutting fluids from entering the interface area. Hence, to enhance the grinding performance, cryogenic cooling has been introduced to improve the penetration into the stiff air layer. The current work investigates the grindability of the ground surface of AISI D2 tool steel under different environments: dry, wet, and cryogenic, regarding grinding forces (i.e. tangential and normal force), specific grinding energy, and surface characterisation. This paper also proposed a method to evaluate image-based Abbott–Firestone curve (bearing area curve) parameters to characterise the ground surface topography. Significant reductions in grinding forces (64%–67% and 44%–50% in Ft, 54%–58% and 34%–39% in Fn), low specific grinding energy (64%–67% and 44%–50%), decrease in surface roughness (46%–51% and 30%–36% in Ra, 37%–41% and 31%–35% in Rz), improved 2D and 3D roughness profiles and higher bearing area ratio (89.54%) were observed at 40 µm downfeed in cryogenic cooling environments compared to dry and wet environments, respectively. Thus, observations show the importance of cryogenic cooling across the experimental domain. © IMechE 2023.